Regulatory Constraints to Agricultural Productivity - Divanbeigi, Raian; Saliola, Federica (World Bank, Washington, DC, 2017)
The economic thinking around the role of agriculture for development has evolved since the 1950s. Over the past decades, the agriculture sector has been rediscovered as a sector with great potential for triggering growth, reducing poverty and inequality, providing food security, and delivering environmental services. This paper contributes to the literature on the determinants of agricultural development by investigating the role played by laws and regulations. First, the paper proposes new measures of regulatory quality and regulatory efficiency in agriculture. Second, the paper employs cross-section data to test the relationship of the proposed measures with agricultural performance. The results indicate that agricultural productivity is on average higher where transaction costs imposed by regulations are lower and where countries adhere to more regulatory good practices. This relationship is stronger when low transaction costs and regulatory good practices are combined.